Pengaruh Tunneling Incentive, Mekanisme Bonus, dan Leverage Terhadap Keputusan Perusahaan Melakukan Transfer Pricing: pada Perusahaan Manufaktur, Perkebunan, dan Pertambangan - Al Hafizil Azhar; Mia Angelina Setiawan (Universitas Negeri Padang, 2021)
The purpose of this study was to examine the effect of tunneling incentives, bonus mechanisms and leverage on transfer pricing decisions. This research includes causative research. The population used in this study are manufacturing, mining and plantation companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique used in this research is purposive sampling technique. There are 54 manufacturing, mining and plantation companies that are used as research samples. The type of data used is secondary data obtained from the official website of the Indonesia Stock Exchange and the official website of each company. The analytical method used is a quantitative method. The results show that the bonus and leverage mechanisms do not have a positive effect on transfer pricing, but the tunneling incentive variable has a positive effect on transfer pricing.